Development of a Village Financial Governance Model (Case Study in Maitara Tengah Village, North Tidore District, Tidore Islands City) - Ache, Samsul Bahri; Huseini, Martani (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to develop an effective and accountable village financial governance model in Maitara Tengah Village, North Tidore District, Tidore Islands City. Departing from the challenges of low accountability, transparency, and participation in village fund management, this study uses a descriptive qualitative approach with a single case study. Data was obtained through in-depth interviews, participatory observation, and document analysis. The findings indicate that limited use of information technology, the absence of reporting SOPs, and weak institutional capacity are the main inhibiting factors. Based on this analysis, this study offers a collaborative-participatory village financial governance model that emphasizes the integration of the role of BUMDes and the village financial information system. This model is expected to be able to increase the efficiency of financial management, strengthen the original village income (PADes), and support the achievement of sustainable development at the regional level. The theoretical contribution of this study lies in enriching governance studies through a practical approach in small villages, while its practical contribution provides concrete recommendations for policy makers in designing an adaptive and sustainable village financial management system.